2016
DOI: 10.1097/aln.0000000000000951
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine versus Propofol Sedation Reduces Delirium after Cardiac Surgery

Abstract: Background Postoperative delirium (POD) is a serious complication after cardiac surgery. Use of dexmedetomidine to prevent delirium is controversial. The authors hypothesized that dexmedetomidine sedation after cardiac surgery would reduce the incidence of POD. Methods After institutional ethics review board approval, and informed consent, a single-blinded, prospective, randomized controlled trial was conducted in patients 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
283
4
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 302 publications
(299 citation statements)
references
References 19 publications
8
283
4
4
Order By: Relevance
“…This is the first study to report on the efficacy of subsedative dose dexmedetomidine to reduce the development of delirium, both in non-intubated patients and in those requiring mechanical ventilation and sedation with γ-aminobutyric acid (GABA) receptor agonists. This study adds to the growing body of evidence that dexmedetomidine can reduce the development of delirium (21)(22)(23). Prior studies, however, compared dexmedetomidine to other sedating agents, either benzodiazepines or propofol.…”
Section: Commentarymentioning
confidence: 92%
See 1 more Smart Citation
“…This is the first study to report on the efficacy of subsedative dose dexmedetomidine to reduce the development of delirium, both in non-intubated patients and in those requiring mechanical ventilation and sedation with γ-aminobutyric acid (GABA) receptor agonists. This study adds to the growing body of evidence that dexmedetomidine can reduce the development of delirium (21)(22)(23). Prior studies, however, compared dexmedetomidine to other sedating agents, either benzodiazepines or propofol.…”
Section: Commentarymentioning
confidence: 92%
“…When used as the primary sedative for intubated medical and surgical ICU patients, dexmedetomidine reduced the duration of delirium when compared to benzodiazepines (21,22). Additionally, in patients undergoing cardiac surgery, dexmedetomidine has been shown to reduce the incidence of postoperative delirium when compared to propofol, leading to a reduction in ICU time and cost related to delirium (23). A recent trial in patients with hyperactive delirium that prevented weaning from mechanical ventilation found that dexmedetomidine increased ventilator-free hours and resolved delirium symptoms faster than placebo (24).…”
mentioning
confidence: 99%
“…The DEXCOM (Dexmedetomidine Compared to Morphine) study randomized such patients to dexmedetomidine or morphine and showed that dexmedetomidine reduced the duration but not incidence of delirium 63. Djaiani et al randomized patients to dexmedetomidine versus propofol and found that dexmedetomidine reduced the incidence of delirium (17.5% versus 31.5%, OR 0.46; P =0.028) and reduced duration (2 days versus 3 days, P =0.04) 64. However, a randomized placebo controlled trial undertaken by Li et al failed to demonstrate any reduction in the incidence of delirium when dexmedetomidine was administered during anaesthesia and during the early postoperative period (4.9% in the dexmedetomidine group versus 7.7% in the control group, P =0.345) 65.…”
Section: Preventionmentioning
confidence: 99%
“…They also found significantly lower total costs with dexmedetomidine, primarily due to decreased ICU stay and reduced mechanical ventilation. Most recently, a randomized controlled trial of dexmedetomidine versus propofol for ICU sedation after cardiac surgery found a decreased incidence and reduced duration of delirium with dexmedetomidine, leading to a reduction in ICU time and cost related to delirium (11). Thus, results from multiple trials examining dexmedetomidine for sedation consistently demonstrate improved delirium outcomes and reduce cost with the use of dexmedetomidine.…”
mentioning
confidence: 75%
“…A promising therapy that can not only treat delirium symptoms but may also prevent the development of delirium is the alpha-2 agonist dexmedetomidine. Several studies have shown that dexmedetomidine, when used for sedation of patients on mechanical ventilation, can reduce the incidence and duration of delirium (8)(9)(10)(11) and hasten extubation of patients with hyperactive delirium (12,13). There is little data, however, on its effectiveness in non-intubated patients.…”
mentioning
confidence: 95%